Coordinating Multi-Level Environmental Governance in Global South: A Communication Architecture Perspective - Ratih Kurnia Hidayati; Kamal; Tirta Nata Adi Wijaya; Dunola Tri Nugraeni (DAWUH : Islamic Communication Journal, 2026)
Environmental governance increasingly depends on coordination across multiple institutional levels; however, such coordination remains difficult to sustain in practice. Existing explanations emphasise institutional design and actor interactions but pay limited attention to how coordination is organised through communication. This study examines how coordination is enacted within a multi-level environmental governance system by analysing communication processes among 60 institutional actors in Indonesia. Using a qualitative approach, the analysis identifies three interrelated dynamics: communicative translation across governance levels, negotiated authority and legitimacy, and the interplay between formal and informal coordination practices. The findings show that coordination is not produced by institutional structures alone but emerges through patterned communication that aligns actors across different levels and sectors. By conceptualising communication as architecture, this study explains how coordination is sustained, stabilised, and adapted within complex and fragmented governance systems.